2019
DOI: 10.30612/agrarian.v12i45.7965
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de semeadora-adubadora de milho de segunda safra em semeadura direta

Abstract: Resumo: A produtividade da cultura do milho depende da qualidade de semeadura que, por sua vez, está relacionada a fatores edafoclimáticos e operacionais. Objetivou-se avaliar o desempenho de uma semeadoraadubadora durante a semeadura e desenvolvimento inicial do milho de segunda safra (Zea mays L.), em plantio direto. Utilizou-se o delineamento inteiramente casualizado em arranjo de parcelas subdivididas, com três repetições, sendo os tratamentos dois sulcadores do solo (disco duplo e haste sulcadora), duas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 12 publications
(20 reference statements)
0
17
0
3
Order By: Relevance
“…In this research, the shape of seeds was not evaluated, however, this variable needs to be better investigated due to different sowing speeds. Souza et al (2019) found decreasing relationships of seed deposition uniformity between velocities 7.2 and 8.6 km h -1 . The authors also noted that furrower depth affects seed deposition.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In this research, the shape of seeds was not evaluated, however, this variable needs to be better investigated due to different sowing speeds. Souza et al (2019) found decreasing relationships of seed deposition uniformity between velocities 7.2 and 8.6 km h -1 . The authors also noted that furrower depth affects seed deposition.…”
Section: Resultsmentioning
confidence: 76%
“…Proper seed deposition in the sowing row, with adequate spacing and depth is known as plantability (Bertelli et al, 2016). Plantability is important for the corn crop, as it determines the crop's productivity (Souza et al, 2019). In addition to sowing, speed and feeder models can affect corn productivity (Cortez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Lambrecht et al (2017) os mecanismos sulcadores têm a função de abrir o sulco e depositar em profundidade adequada o fertilizante e a semente, proporcionando condições ideais para germinação, emergência e crescimento da planta. O desenvolvimento inicial das plântulas depende de um bom leito de semeadura e do microclima em torno da semente, fatores Research, Society and Development, v. 11, n. 6, e20111628789, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i6.28789 3 que podem ser alterados pelo uso dos diferentes mecanismos de abertura de sulco (Santos et al, 2016;Souza et al, 2019).…”
Section: Introductionunclassified
“…Sowing quality is related to such operational factors as the furrowing mechanism of the planter-fertiliser, displacement speed, and sowing depth (SOUZA et al, 2019). When sowing maize, these settings are even more important due to productivity being strongly dependent on seed distribution by the planter (VIAN et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The type of furrowing mechanism together with furrowing depth can affect the speed of emergence index and the population of maize plants per hectare (SOUZA et al, 2019). Due to its role in turning the soil, the type of furrower influences the tractive force (TRICAI et al, 2016), with shanks possibly requiring greater tractive effort than discs (FRANCETTO et al, 2015;MILAGRES et al, 2016).…”
Section: Introductionmentioning
confidence: 99%